Feasibility of a group-based laughter yoga therapy on anxiety and happiness among community-dwelling older adults: A quasi-experimental study - Mona Metwally El-Sayed; Sarah Ali Hafez; Abdulqadir J. Nashwan; Mahmoud Abdelwahab Khedr; Ayman Mohamed El-Ashry (Elsevier, 2024)
Background: Applying a unique, non-pharmacological therapy for community-dwelling older adults, such as Laughing Yoga Therapy, may have a considerable impact on their anxiety, happiness, and psychological well-being. Aim of the study: To investigate the feasibility of applying Laughing Yoga Therapy interventions to anxiety and happiness among community-dwelling older adults. Methodology: A quasi-experimental design was used on a convenient community-dwelling. Older adult participants were selected to undergo eight sessions over four weeks. The Geriatric Anxiety Scale and Arabic Scale of Happiness were used to evaluate the participants' anxiety and happiness levels. Results: A statistically significant decrease in anxiety level among the study group compared to the control group (Pre = 16.68 (7.35), immediate = 6.65 (2.89), post three-month = 7.68 (2.75), p=<0.001 and effect size = 0.715). As well as an increase in happiness level among the study group compared to the control group were found (pre = 54.23 (6.60), immediate = 62.05 (4.09), post three-month = 61.95 (4.38), with statistical significant= <0.001 and effect size = 0.677. Conclusion and recommendations: Participation in laughing yoga therapy significantly reduced anxiety and increased happiness among elderly people. These findings suggest incorporating laughing yoga therapy into nursing interventions offered to older adults in nursing homes and community groups.